Coupling enzymatic digestion with nanopore sensing for low-abundance EGFR-L858R mutation detection - Yan, Ling; Wang, Zhenxin; Yin, Yajie; Niu, Changchun; Luo, Yang (Frontiers in Bioengineering and Biotechnology, 2025)
Single nucleotide variants (SNVs) serve as crucial biomarkers for tumor diagnosis, treatment, and prognosis. However, their detection remains challenging due to the low mutation frequency and limited abundance. In this study, we developed a sensitive and efficient SNV detection method combining T7 endonuclease I (T7E1) digestion and nanopore detection. The assay was designed to detect the L858R mutation in exon 21 of the EGFR gene, a key driver mutation in various cancers. Magnetic bead probes were utilized to capture and purify target DNA, followed by enzymatic cleavage and nanopore detection. The optimal nanopore detection voltage was determined to be 500 mV, ensuring a clear and reproducible signal for identifying digested DNA fragments. This approach enabled the detection of L858R mutations with a sensitivity as low as 0.1%. Compared to conventional sequencing and digital PCR, our method is simple, time-efficient, and cost-effective. This strategy offers a promising platform for SNV detection, providing a valuable tool for tumor diagnosis and personalized treatment.